Histopathological Grading based on Tumor Margin according to BI-RADS Mammography in Breast Cancer - Ayasha, Shabrinna; Mardiyana, Lies; Utomo, Budi; Ali, Iskandar (Universitas Airlangga, 2024)
Highlights: The highest distribution of breast cancer patients’ age based on the 5-year age interval was 45- 49 years old. There was no significant difference between tumor margin and age of breast cancer patients. There was no significant difference between tumor margin and histopathological grade. Abstract Introduction: Mammography is an X-ray technique used to take images of the breast. It is the primary diagnostic method for breast tumors. Breast imaging reporting and data system (BI-RADS) classification is needed to determine benign or malignant masses by accessing the mass's shape, margin, density, and other features. However, the tumor margin is the most helpful one. This study aimed to know the difference in the distribution of tumor margin types in each histopathological grading in breast cancer patients. Methods: This was an observational analytic study with a comparative approach using secondary data from medical records of patients with breast cancer at the radio diagnostic and anatomical pathology installation of Dr. Soetomo General Academic Hospital, Surabaya, from January 2017 to December 2021. All statistical data were performed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 27, with a p<0.05 considered statistically significant. Results: Out of 235 cases, the highest distribution of breast cancer patients’ age interval was 45-49 years old (20.9%), the primary tumor margin type was spiculated (64.3%), and the highest distribution of histopathological grading was grade 3 (53.2%). There was no significant difference between tumor margin and age of breast cancer patients (p=0.815), with spiculated tumor margin as the most common type in all age intervals. There was no significant difference (p=0.163) in the distribution of tumor margin types in each histopathological grading, with spiculated tumor margin as the most common type in every grade. Conclusion: There was no significant difference between tumor margin and age of breast cancer patients, and there was no significant difference between tumor margin and histopathological grading.